Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Characterization of a newly isolated freshwater Eustigmatophyte alga capable of utilizing far-red light as its sole light source - Benjamin M. Wolf; Dariusz M. Niedzwiedzki; Nikki Cecil M. Magdaong; Robyn Roth; Ursula Goodenough; Robert E. Blankenship (Photosynthesis Research, 2018)

Quantitative biogeography of picoprasinophytes establishes ecotype distributions and significant contributions to marine phytoplankton - Alexander J. Limardo; Sebastian Sudek; Chang Jae Choi; Camille Poirier; Yoshimi M. Rii; Marguerite Blum; Robyn Roth; Ursula Goodenough; Matthew J. Church; Alexandra Z. Worden (Environmental Microbiology, 2017)
Summary Bathycoccus and Ostreococcus are broadly distributed marine picoprasinophyte algae. We enumerated small phytoplankton using flow cytometry and qPCR assays for phylogenetically distinct Bathycoccus clades BI and BII and Ostreococcus clades OI and OII. Among 259 photic‐zone samples from transects and time‐series, Ostreococcus maxima occurred in the North Pacific coastal upwelling for OI (36 713 ± 1485 copies ml −1 ) and the Kuroshio Front for OII (50 189 ± 561 copies ml −1 ) and the two overlapped only in frontal regions. The Bathycoccus overlapped more often with maxima along Line‐P for BI (10 667 ± 1299 copies ml −1 ) and the tropical Atlantic for BII (4125 ± 339 copies ml −1 ). Only BII and OII were detected at warm oligotrophic sites, accounting for 34 ± 13% of 1589 ± 448 eukaryotic phytoplankton cells ml −1 (annual average) at Station ALOHA's deep chlorophyll maximum. Significant distributional and molecular differences lead us to propose that Bathycoccus clade BII represents a separate species which tolerates higher temperature oceanic conditions than Bathycoccus prasinos (BI). Morphological differences were not evident, but quick‐freeze deep‐etch electron microscopy provided insight into Bathycoccus scale formation. Our results highlight the importance of quantitative seasonal abundance data for inferring ecological distributions and demonstrate significant, differential picoprasinophyte contributions in mesotrophic and open‐ocean waters.

Assessment of Juvenile Pigs to Serve as Human Pediatric Surrogates for Preclinical Formulation Pharmacokinetic Testing - Wyatt J. Roth; Candice B. Kissinger; Robyn R. McCain; Bruce R. Cooper; Jeremy N. Marchant-Forde; Rachel C. Vreeman; Sophia Hannou; Gregory T. Knipp (The AAPS Journal, 2013)